Social discounting, social costs of carbon, and their use in energy system models. (16th September 2021) - Löffler, Konstantin
Abstract: Discounting plays a large role in cost-optimization models, but is nevertheless often only covered in little detail in energy system models. The aim of this paper is to highlight the effects of varying discount rates and social costs of carbon in energy system models with the example of the Global Energy System (GENeSYS-MOD), propagating open debate and transparency about chosen parameters for model applications. In doing so, this paper adds to the academic discourse on socio-economic factors in energy system models and gives an outline to modelers in the field by providing example results. The results show that close-to-zero discount rates that factor in intergenerational equality, total emissions could be reduced by up to 41% until 2050 compared to the baseline discount rate of 5%. This effect is even increased when a carbon price akin to the actual social costs of carbon is chosen. This underlines the importance of the topic, which is, up to now, seldom covered in cost-optimizing energy system models.